Honduras : First Review Under the Stand-By Arrangement and Under the Standby Credit Facility-Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for Honduras. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The authorities' remain committed to lower the fiscal deficit and stabilize the public debt-to-GDP ratio at 30 percent of GDP while improving the quality of expenditure. The authorities agree to maintain public expenditure within the ceilings established in the 2011 budget. Further progress in public sector reform is essential for improving the efficiency and sustainability of public finances. Progress has been made in improving the government's debt management strategy. The central bank has prepared a plan for upgrading the monetary policy framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet